Developing Augmented Reality of Virus as Learning Media - Ghazi, M Ikhsan Al; Paidi, Paidi; Wibowo, Yuni (Universitas Ahmad Dahlan, 2022)
This This study aims to: (1) develop Augmented Reality Virus (ARVI) as learning media for class X students; (2) determine the feasibility of learning media Augmented Reality virus (ARVI). The method used in this research is Research and Development with the ADDIE model limited to the Development stage. Product assessment is carried out by lecturers of material experts, lecturers of media experts, and biology teachers, each of which consists of two people. The limited trial was conducted on 18 students grade XI. Data were collected using a questionnaire and if necessary interviews were conducted with the informants. The data analysis was done quantitatively. The results of this study resulted in a product in the form of an Android application containing Augmented Reality feature that can display 3-dimensional illustrations of viruses that can be rotated and adjust the magnification when directed at the marker. Applications developed can run on the Android operating system 6 and above. The developed learning media has very feasible criteria. This is based on the results of the validation of material experts of 98.71%, media experts of 77.60%, biology teachers 91.31%, and students of 83.96%.